Functional Ingredients from Agri-Food Waste: Effect of Inclusion Thereof on Phenolic Compound Content and Bioaccessibility in Bakery Products - Valentina Melini; Francesca Melini; Francesca Luziatelli; Maurizio Ruzzi (MDPI AG, 2020)
Reducing food loss and waste is among the efforts to relieve the pressure on natural resources and move towards more sustainable food systems. Alternative pathways of food waste management include valorization of by-products as a source of phenolic compounds for formulation of functional foods. Bakery products may act as an optimal carrier of phenolic compounds upon fortification. The aim of this paper is to present and discuss the effect that the inclusion of functional ingredients from agri-food waste can have on phenolic content and bioaccessibility in bakery products. To this aim, methods for the recovery of phenolic compounds from agri-food waste are presented, and fortification of bakery products by waste from fruits, vegetables, and seed crops is discussed. Bioaccessibility studies on fortified food products are considered to identify gaps and needs in developing sustainable healthy foods. Fruit and vegetable by-products are among the food wastes mostly valorized as functional ingredients in bakery product formulation. Agri-food waste inclusion level has shown to correlate positively with the increase in phenolic content and antioxidant capacity. Nevertheless, further studies are required to assess bioaccessibility and bioavailability of phenolic compounds in enriched food products to estimate the potential of agri-food waste in promoting human health and well-being.